Too Hard to Find with Too Little Time: What School Social Workers Want in Online Resources for Evidence-Based Practice - Michele Patak-Pietrafesa; Natasha K Bowen; Ashley E Stewart; Michael S. Kelly (International Journal of School Social Work, 2019)
School mental health practitioners, including social workers, are mandated through federal, state, and professional entities to provide evidence-based practices to students. Nevertheless, rates of use of evidence-based practices among mental health professionals in schools remain low, even as knowledge about effective practices increases. This study aimed to further knowledge about how to promote and support the use of evidence-based practices among school practitioners using online technology. School social workers attending a summer professional development event took part in focus groups exploring (a) their current perceptions of evidence-based practices, (b) their experiences finding evidence-based practice information online, and (c) their preferences for the formatting and content of online resources. Participants described a willingness to use evidence-based practice, efforts to find information, and difficulties encountered with online sources. Preferences for readily available, searchable, brief, and understandable online information were expressed. Implications for meeting the needs of school social workers with online resources are discussed.
Keywords: Focus Group; School Social Work; Evidence Based Practice; Technology